Temporal changes in tree community structure and richness in a seasonally dry tropical forest in Minas Gerais, southeastern Brazil - Santos, Paola F; Garcia, Paulo O; Santos, Rubens M; Morel, Jean D; Benício, Matheus H; Apgaua, Deborah M; Tng, David Y (BOSQUE, 2017)
Seasonally Dry Tropical Forests (SDTF) are gaining recognition as a habitat of global conservation significance. However, these forests often occur on rich soils, and are therefore prone to disturbance by agricultural activities. Across their range, many SDTFs are in various stages of regeneration, although little is known about their regeneration dynamics and temporal change in general. To fill this knowledge gap, we studied the changes in species diversity and community structure of an SDTF tree community with a history of past selective logging located in northern Minas Gerais, Brazil. We hypothesized an increase in species diversity and biomass-related parameters, along with a reduction in stem density for the community after five years of regeneration. In 2005, we measured all tres (diameter ≥ 3.18 cm at 1.3 m) within twenty 20 x 20 m (400 m²) plots in the patch, and we remeasured the trees in 2010. Between the two censuses, we found no significant changes in species richness and diversity, suggesting that species accumulation had leveled out. However, we found significant gains in tree basal area and recruitment, suggesting continual regeneration. Diameter class distributions of the five most abundant tree species showed similar patterns. We conclude that past disturbances can have ongoing effects on SDTF vegetation, although inter-annual variations may also play a regulatory role on community dynamics.